MANAJEMEN KONFLIK DALAM PENINGKATAN PRODUKTIVITAS DI AKADEMI KEBIDANAN MUHAMMADIYAH BANDA ACEH - Yuliani Ibrahim; Jamaluddin Idris; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Conflict is normal and sometimes cannot be unavoided in an organization. The current beliefs consider that a conflict is not merely a disadvantage but it can bring advantages to the organization if it is well-controlled. Conflict management is a conflict resolution under pressure and in emotional environment. The objective of this research is to find out (1) the types of conflict; (2) sources of conflict; (3) director point of view regardingthe form of conflict; (4) approaches for conflict management; and (5) organization productivity at Muhammadiyah Midwifery Academy of Banda Aceh. This research is a descriptive research with qualitative approach. The data were collected by doing interview, observation and documentation study. The research results show that (1) there were some types of conflicts at Muhammadiyah Midwifery Academy such as interpersonal conflict, conflict between two persons and conflict between two groups; (2) the sources of conflict are communication, different interest, and interdependency on working activities; (3) the form of conflict was the functional conflict which influenced the improvement of organization performance; (4) the approach conducted by the director was the approach of conflict simulation, conflict controlling, and conflict resolution and elimination, and (5) the conflict management applied at Muhammadiyah Midwifery Academy was one of the efforts which influenced the organization productivity.Keywords: conflict management and organization productivity